Can Resilience Assessments Inform Early Design Human Factors Decision-making?. Issue 29 (2022) - Irshad, Lukman; Hulse, Daniel
Abstract: There is a growing call among researchers for tighter coupling between human factors and human reliability assessments. In this research, we explore how early design stage resilience simulation can help bridge the gap between human factors and human reliability assessments. Resilience is the ability of a system to proactively mitigate potentially hazardous events, involving the system's adaptive capacity to enable both active prevention and recovery. The fmdtools toolkit allows designers to assess the resilience of a system by modeling the human error and machine-related failure propagation across sets of fault scenarios and operational/environmental parameters during the early design stages. This toolkit has a number of constructs that enable the early-stage, low-fidelity dynamic human reliability assessment, including action sequence graphs and human performance degradation models. In this paper, we study how fmdtools simulations and analyses can help inform and prioritize human factors design decision-making, resulting in tighter coupling between human factors and human reliability assessments. Specifically, we explore the results from a rover design example to understand the types of information that can help guide human factors-related decision-making.